Pattern of Crop damage by Asian Elephants (Elephas maximus) in Bandipur National Park - Lingaraju, H. G.; Venkataraman, G. V. (Indian Forester, 2020)
Recorded incidence of confiict between humans and elephants, crop-raiding, is increasing in rural Africa and Asia. This study analysed crop-raiding by Asian elephants (Elephas maximus) around Bandipur National Park consisting of 107 villages during April 2011 to March 2014. Our resuits show that, 2,099 crop incidents were reported during our study period. Many cultivated crops were damaged, and they are categorized into seasonal and plantation crops. Among seasonal crops, the loss ofragi (723 quintals) was highest, followed by tomato (670 quintal) and red gram (397 quintal). Among the plantations, the damage to banana plants was highest (10656 plants), followed by coconut tree (308 plants) and mango plants (94 plants). The relative raiding frequency of sugarcane crop by elephants was found to be highest (21%) followed by ragi (15%) and banana. Ten crop species were included in the category of â€œOther cropsâ€ and contributed to 13% of all incidents. Net economic loss for both seasonal and annual crops damage was estimated high for the year 2012-13 (INR 27, 08,717) followed by 2011-12 (INR 16, 30,012) and 2013-14 (INR 15, 36,023). Crop damage displays broad inter-year variation, it was highest in December and lesser incidents during April and May.